2006
DOI: 10.1017/s1074070800022331
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Effects of an Urban Growth Boundary on Land Development

Abstract: This study estimates the effects of an urban growth boundary (UGB) on land development decisions in Knox County, TN, using a heteroscedastic probit model. With combined effects of increased land development within the city boundary and decreased development within the UGB and the neighboring town of Farragut after the implementation of UGB, the UGB of Knox County has been successful in urban revitalization within the city boundary and discouraging urban sprawl. These UGB impacts may be related to the city gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…This outcome was inconsistent with our expectations and some previous studies on UGBs. Containment shifts development from exurban and rural areas to suburban and urban areas because of containment boundaries [51,52]. This outcome may have been because UGBs usually surround mono-centric cities, whereas Seoul is a poly-centric city.…”
Section: Basic Regression Results and Analysismentioning
confidence: 99%
“…This outcome was inconsistent with our expectations and some previous studies on UGBs. Containment shifts development from exurban and rural areas to suburban and urban areas because of containment boundaries [51,52]. This outcome may have been because UGBs usually surround mono-centric cities, whereas Seoul is a poly-centric city.…”
Section: Basic Regression Results and Analysismentioning
confidence: 99%
“…Some studies suggest that UGBs have effectively slowed down sprawling development (e.g., Kline, 2005;Kline and Alig, 1999;Nelson et al, 1997;Patterson, 1999;Cho et al, 2006). Other studies found that UGBs have no impact on growth (e.g., Jun, 2004;.…”
Section: Introductionmentioning
confidence: 99%
“…Cho and others (Cho et al. , ; Cho, Poudyal, and Lambert ) conduct a series of empirical analyses measuring the effects of UGB in Knox County, Tennessee by applying econometric techniques. In an early study (Cho et al.…”
mentioning
confidence: 99%
“…In an early study (Cho et al. ), a pooled data set is used and suggests that the UGB is effective in controlling sprawl. However, in recent analyses (Cho et al.…”
mentioning
confidence: 99%